Simple models of the weak-nonlinear stage for equations with random coefficients - Grachev, D.A.; Zhdanov, A.G. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2012)
The paper deals with some nonlinear equations on the basis of which the intermittency effects are reproduced. The problem on the minimum value of independent realizations required for the numerical simulation of statistical moments of solutions is studied. It is shown that this value rapidly decreases with increasing nonlinearity.